Care of Voiding Dysfunction in Rehabilitation and Convalescent Hospitals - Seong Hyeon Yu; Eu Chang Hwang; Seung Il Jung (Urogenital Tract Infection)
The number of rehabilitation and convalescent hospitals is increasing rapidly; the primary goal of these institutions is to manage patients’ chronic disorders and maintain their daily functions. Most patients in these hospitals are elderly and experience difficulties related to behavior, communication, or cooperation because of various co-existing chronic medical diseases. Therefore, urologic problems may be more prevalent in these hospitals compared to other hospitals. On the other hand, unlike the medical management of other chronic medical problems, urologic problems have been neglected. This situation could increase the secondary complications, decrease the quality of life, and exacerbate co-existing conditions among such patients. Therefore, this review investigates problems concerning voiding dysfunction-related care in rehabilitation and convalescent hospitals and seeks solutions to overcome them.